Uticaj pomoćnika za kontrolu glikemije uz pomoć MMC-a na biohemijske pokazatelje metabolizma glukoze kod dijabetesa tipa 2: retrospektivna studija: MMC-Based Intervention Improves Glucose Metabolism Biomarkers - Shen, Peipei; Yang, Hongjiao (Journal of Medical Biochemistry, 2025)
Background: Accurate biochemical monitoring is central to effective diabetes management. This study investigated the effect of the National Standardized Metabolic Management Center (MMC)-assisted glycemic control assistant on laboratory-based glucose metabolism parameters in patients with type 2 diabetes. Methods: A retrospective study was conducted on 160 patients with type 2 diabetes, including 95 who received MMC-assisted digital management and 65 who received routine care. Key biochemical parameters—fasting plasma glucose (FPG), 2-hour postprandial glucose (2hPG), and glycated hemoglobin (HbA1c)—were measured using standardized enzymatic assays. Dietary behavior and diabetes self-management were also assessed using validated scales. Results: Baseline biochemical markers and behavioral scores showed no significant differences between groups. After intervention, the MMC-assisted group demonstrated significantly lower levels of FPG (7.42±2.43 vs. 8.30±2.66 mmol/L, P=0.032), 2hPG (10.23±3.21 vs. 12.39±3.50 mmol/L, P<0.001), and HbA1c (7.26±2.05% vs. 7.98±2.34%, P=0.041) compared to controls. Improvements were also observed in dietary behavior and self-management, including better adherence to blood glucose monitoring and medication. Conclusion: The MMC-assisted glycemic control assistant significantly improves biochemical markers of glucose metabolism in patients with type 2 diabetes. This laboratory-confirmed improvement supports the integration of digital tools into standardized metabolic disease management.